On Energy of Prime Ideal Graph of A Commutative Ring Associated with Seidel-Based Matrices - Romdhini, Mamika Ujianita (IndoMS, 2025)
Some energies of the prime ideal graph are found for a commutative ring associated with Seidel-based matrices including Seidel, Seidel Laplacian, and Seidel signless Laplacian matrices.